Literasi Kesehatan Mental dan Stigma Publik Sebagai Prediktor Sikap Terhadap Bantuan Psikologis Pada Mahasantri - Malisa Falasifah; Diany Ufieta Syafitri (Universitas Andalas, 2021)
Abstract. This study aimed to examine the relationship between mental health literacy and public stigma with attitudes towards psychological help among Mahasantri Pesanmasa Unissula Semarang. A sample of 225 respondents as the research trial and 174 respondents as the research sample were involved in this study. The sampling technique used cluster sampling. The measuring instrument consisted of the attitude scale towards psychological help a= 0,720, mental health literacy scale a= 0.814 and public stigma scale a= 0,724. The data analysis technique used multiple regression and partial correlation. The results of the first hypothesis test obtained R= 0.286 and F= 7.608 with p= 0,001 (p<0,01) showed that mental health literacy was able to significantly predict attitudes towards psychological help among Mahasantri. The first partial test between mental health literacy and attitudes towards psychological help obtained rx1y= 0.253, p= 0,001 (p<0,01), showed that there was a relationship between mental health literacy and attitudes towards psychological help while the second partial test between public stigma and attitudes towards seeking profesional psychological help obtained rx1y= -0,043 p= 0,570 (p>0,05), meaning that there was no relationship between public stigma and attitudes towards psychological help among Mahasantri. Keywords: Attitudes towards psychological help, mental health literacy, public stigma, college students